Classificação dos veios quartzo-carbonáticos de depósitos auríferos no lineamento Córrego do Sítio, QF, MG - Marco Aurelio Sequetto Pereira (2013)
The orogenic-type, lode-gold deposits Cachorro Bravo, Laranjeiras and Carvoaria, associated with the Córrego do Sítio (CdS) regional lineament are located in the eastern portion of the Quadrilátero Ferrífero region, southern São Francisco craton, Brazil. They are hosted in Archean metaturbiditic rocks of the Rio das Velhas greenstone belt and controlled by NE-SW shear zones. Pre- to post-deformational dikes/sills are closely related to gold mineralization and constitute excellent prospective guides in these regional lineaments such as CdS. Five vein systems have been classified, V1 to V5, in accordance to their mineralogical composition, texture, orientation, spatial distribution and geometry. Two types of quartz occur in these veins, with type 1 being predominantly smoky, early hydrothermal, and type 2 a milky, recrystallized quartz. Only V1 veins (fault-fill vein) are related to gold and have a paragenesis with arsenopyrite+pyrite+pyrrhotite+berthierite+ free gold; they develop along the mylonitic foliation S1m, and have been deformed. The V2 veins (oblique-extension veins) are associated temporally with V1 and although non-mineralized, in the studied deposits they are contemporaneous to the gold stage. These two systems are formed under a ductile-brittle regime. The V3 veins (extension and breccias veins) are post gold and represent a late-stage hydrothermal fluid under ductile-brittle to brittle regime; they may be related to changes in the stress field and to the emplacement of late-stage Db1 dikes. The V4 veins (extension veins) have mineral replacement reactions that represent hydration of the system associated with the relaxation of the compressive field. The V5 veins (stockwork style) are limited to metamafic Db1 dykes/sills and fluid inclusion studies indicate that they contain a different fluid from the others systems.